Organic–inorganic polyimide nanocomposites containing a tetrafunctional polyhedral oligomeric silsesquioxane amine: synthesis, morphology and thermomechanical properties. Issue 3 (5th January 2018) - Qiu, Junjun; Xu, Sen; Liu, Ning; Wei, Kun; Li, Lei; Zheng, Sixun
Abstract: 5, 11, 14, 17‐Tetraanilinooctaphenyl double decker silsesquioxane, a well‐defined tetraamino polyhedral oligomeric silsesquioxane (POSS), was synthesized in this work. This novel tetrafunctional POSS amine was employed to prepare polyimide nanocomposites. It was found that the hybrid polyimide nanocomposites displayed nanostructures in which the POSS component was aggregated into spherical microdomains with a diameter of 40 − 80 nm. Compared to unmodified polyimide, the POSS‐containing polyimide nanocomposites displayed improved thermal stability and surface hydrophobicity. Owing to the introduction of the POSS microdomains, the dielectric constants of the polyimide nanocomposites were significantly decreased in comparison with plain polyimide. © 2017 Society of Chemical Industry Abstract : Organic–Inorganic Polyimide Nanocomposites Containing a Tetrafunctional Polyhedral Oligomeric Silsesquioxane Amine: Synthesis, Morphology and Thermomechanical Properties.